2015
DOI: 10.1016/j.atmosenv.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological detrending of primary and secondary pollutant concentrations: Method application and evaluation using long-term (2000–2012) data in Atlanta

Abstract: The effectiveness of air pollution regulations and controls are evaluated based on measured air pollutant concentrations. Air pollution levels, however, are highly sensitive to both emissions and meteorological fluctuations. Therefore, an assessment of the change in air pollutant levels due to emissions controls must account for these meteorological fluctuations. Two empirical methods to quantify the impact of meteorology on pollutant levels are discussed and applied to the 13-year time period between 2000 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 19 publications
2
31
0
Order By: Relevance
“…From 2005 to 2014, S4 showed a decreasing trend, which may be attributed to long-term reductions in regional SO 2 emissions due to rules such as the Clean Air Nonroad Diesel Rule and the Acid Rain Program for utilities. Similar long-term decreasing trends of atmospheric sulfate in the U.S. have been reported in other studies and have been linked to the implementation of a number of regulations and associated controls on sulfur emissions in the U.S. (Hubbell et al, 2009;Henneman et al, 2015).…”
Section: S4: Sulfate/industrial (30% Of Pm25)supporting
confidence: 77%
“…From 2005 to 2014, S4 showed a decreasing trend, which may be attributed to long-term reductions in regional SO 2 emissions due to rules such as the Clean Air Nonroad Diesel Rule and the Acid Rain Program for utilities. Similar long-term decreasing trends of atmospheric sulfate in the U.S. have been reported in other studies and have been linked to the implementation of a number of regulations and associated controls on sulfur emissions in the U.S. (Hubbell et al, 2009;Henneman et al, 2015).…”
Section: S4: Sulfate/industrial (30% Of Pm25)supporting
confidence: 77%
“…Meanwhile, part of Henneman, Shen, et al (2017) examined observed OPEs (ΔO 3 /ΔNO z ) in the southeast United States from 1996 to 2015 using data from the same SEARCH sites as Blanchard and Hidy (2018). At each SEARCH site, the authors applied a long-term meteorological detrending of observed [O 3 ] concentrations to approximate the upper 20th percentile for photochemical state or PS*, a parameter that the authors claim (1) describes daily photochemical activity and (2) is independent of emissions (Henneman et al, 2015;Henneman, Chang, et al, 2017;Henneman, Shen, et al, 2017). Then, Henneman, Shen, et al (2017) estimated observed OPEs over the 20-year period using daily 14:00-15:00 local time averages of NO x , NO y , and O 3 for days corresponding to the upper 20th percentile for PS*.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical analysis of ambient air quality data is another commonly used method to decouple the meteorological effects on air quality (Henneman et al, 2017;Liang et al, 2015), including Kolmogorov-Zurbenko (KZ) filter model and deep neural network (Wise and Comrie, 2005;Comrie, 1997;Eskridge et al, 1997;Hogrefe et al, 2003;Gardner and Dorling, 2001). But they usually gave a poor fitting, suggesting a poor performance of the KZ filter model, or did not allow us to investigate the effect of input variables in neural network models (therefore it is referred as a "black-box" model) (Gardner and Dorling, 2001;Henneman et al, 2015). More recently, new approaches based on classification trees are being developed, which are suitable for air quality weather detrending, including the boosted regression trees (BRT) and random forest (RF) algorithms (Carslaw and Taylor, 2009;Grange et al, 2018).…”
Section: Introductionmentioning
confidence: 99%